2018
DOI: 10.1111/jnp.12161
|View full text |Cite
|
Sign up to set email alerts
|

Intellectual and cognitive profiles in patients affected by schizophrenia

Abstract: Intellectual abilities display high heterogeneity in patients with schizophrenia that might depend on the interaction among neurodevelopmental processes, environmental factors and neurocognitive decline. This study aimed to disentangle the interplay between intellectual level, cognitive status and each cognitive domain, with a focus on speed-related abilities, also including pre-morbid factors. In details, by means of cluster analysis, we identified both in global sample of 452 patients affected by schizophren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 46 publications
2
16
0
Order By: Relevance
“…The total sample size per study ranged from 62 to 8231 individuals irrespective of participants' diagnostic status. The reported clustering methods were Kmeans or non-hierarchical clustering analysis 21,53,55,[69][70][71][72][73][74][75][76] , Ward's method or hierarchical analysis [77][78][79][80][81][82][83] , K-means clustering and Ward's method 18,38,54,[84][85][86][87][88][89] , latent class or profile analysis 15,90,91 and two-step cluster analysis [92][93][94] . One study 95 identified clusters using a combination of clinical/empirical and statistical clustering methods.…”
Section: Cross-sectional Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The total sample size per study ranged from 62 to 8231 individuals irrespective of participants' diagnostic status. The reported clustering methods were Kmeans or non-hierarchical clustering analysis 21,53,55,[69][70][71][72][73][74][75][76] , Ward's method or hierarchical analysis [77][78][79][80][81][82][83] , K-means clustering and Ward's method 18,38,54,[84][85][86][87][88][89] , latent class or profile analysis 15,90,91 and two-step cluster analysis [92][93][94] . One study 95 identified clusters using a combination of clinical/empirical and statistical clustering methods.…”
Section: Cross-sectional Studiesmentioning
confidence: 99%
“…One study 95 identified clusters using a combination of clinical/empirical and statistical clustering methods. The model selection criteria or similarity metrics were visual inspections of the dendrogram, Pearson correlation, (Table 2), 22 studies 18,38,53,54,70,71,75,76,[78][79][80][81][82]84,[86][87][88][90][91][92][93][94][95] reported cognitive clusters in patients with first-episode, stable or chronic schizophrenia with or without antipsychotics treatment and one study 54 reported cognitive clusters in unaffected siblings. Other studies investigated trajectories of negative symptoms 15,85 , positive symptoms 83 , positive and negative symptoms 21,69,77 in patients and positive and negative schizotypy in a nonclinical population 55,72,73,83 .…”
Section: Cross-sectional Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…101,102 In addition, poor cognitive impairment cluster(s) were predicted by age, gender, non-Caucasian ethnicity, low socioeconomic and educational status, poor premorbid adjustment, low premorbid and current IQ, early age of illness onset, long duration of illness, severe positive and negative symptoms, poor social cognition, high antipsychotics dosage, use of second generation antipsychotics, and poor functioning and poor quality of life. 32,37,65,66,[79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95][96] Siblings subgroups with impaired neurocognitive function were predicted by young age, low educational status, low IQ, poor premorbid adjustment, and severe positive schizotypy (Figure 4). 66 Figure 4: Schizophrenia spectrum circle illustrating predictors of symptomatic clusters.…”
Section: Predictors Of Symptomatic Clustersmentioning
confidence: 99%
“…Schizophrenia is a heterogeneous disorder associated with varying clinical and cognitive profiles (6). Though the majority of patients with schizophrenia exhibit some general cognitive dysfunction compared to antecedent expectations, such as premorbid intelligence (7, 8), there is evidence that approximately a quarter of patients display cognitive performance comparable to healthy controls (9–12). Recent evidence has indicated that these “normally” performing patients are significantly less likely to exhibit changes in cognition when participating in CIAS trials (13, 14), suggesting that inclusion of these individuals may limit the scope to detect a pro-cognitive efficacy signal.…”
Section: Introductionmentioning
confidence: 99%